Nonlinear adjustment effects in the purchasing power parity - Andrew Phiri (Economics and Econometrics Research Institute (EERI), 2017)
This study examines nonlinear adjustment effects in the purchasing power parity (PPP) between South Africa and her main currency trading partners; namely, the US, the UK, the Euro area, China and Japan. We use monthly data of the nominal exchange rates and domestic price level data collected between the periods 1971-2014. The empirical study is conducted using nonlinear unit root and asymmetric cointegration analysis. Our empirical results show significant asymmetric PPP effects between South Africa and her main trading partners with causal effects flowing from exchange rates to price differentials.
Keywords: B22; C22; C32; E31; E58; F31; 330; Purchasing power parity (PPP); Threshold co-integration; Momentum threshold autoregressive (MTAR) model; Threshold Error correction (TEC) model; South Africa